Penerapan Kontrak Belajar di SD Muhammadiyah 1 Limboto - Ratna Botutihe; Moon Hidayati Otoluwa; Lia Nurhayati (Transbahasa, 2026)
This study aims to describe the implementation of learning contracts at Muhammadiyah 1 Limboto Elementary School and their role in improving students’ learning discipline. This study employed a qualitative descriptive approach. The research subjects consisted of the principal, fourth-, fifth-, and sixth-grade homeroom teachers, as well as students from grades IV, V, and VI of Muhammadiyah 1 Limboto Elementary School. Data were collected through observation, interviews, and documentation. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that learning contracts were developed collaboratively through agreements between teachers and students at the beginning of the learning process. The contracts contained classroom rules, rights and responsibilities, as well as consequences that had to be followed during learning activities. The implementation of learning contracts provided clear expectations regarding student behavior and helped students understand their responsibilities in the learning process. Furthermore, learning contracts contributed to the improvement of students’ learning discipline, as reflected in their compliance with classroom rules, punctuality in completing assignments, increased attention during lessons, and reduced disruptive behavior. Therefore, the implementation of learning contracts can serve as an effective strategy for fostering discipline, strengthening students’ character development, and creating an orderly and conducive learning environment in elementary schools.